Rahmatan lil Alamin Islamic Value Education Model based on Muhammadiyah School Culture - Parjiman, Parjiman; Sutarman; Muhammad Ragil Kurniawan; Sutrisno; Kun Hidayat (Universitas Islam Negeri (UIN) Salatiga, 2023)
This research is prompted by the prevalence of child delinquency cases, encompassing issues such as bullying, lack of manners, and early-age smoking. Concerns arise regarding the potential implications of these juvenile delinquencies on subsequent behaviors in adolescence. The primary objective of this study is to delve deeper into the Rahmatan Lil Alamin Islamic values education model based on Muhammadiyah school culture at the Muhammadiyah Flagship Elementary School. The focus is on understanding the role of schools in instilling character values and exploring the benefits of the Rahmatan Lil Alamin Islamic values education model within the context of Muhammadiyah school culture, particularly in strengthening character values at the Lemahdadi Muhammadiyah Leading Primary School. This research employs a qualitative methodology with a descriptive analysis approach. Data collection, analysis, and description occur simultaneously to address the formulated problem. The research findings reveal that programs rooted in Muhammadiyah school culture, including strengthening students' daily worship, Hizbul Wathan training, sacred footprint training, leadership training, market day, Tahfidz Qur'an, and language strengthening in foreign and regional languages, effectively instill the Islamic values of Rahmatan Lil Alamin in students. Teachers play a crucial role in this process through integration into school culture and internalization in religious activities. The various models of Rahmatan Lil Alamin Islamic values education, grounded in Muhammadiyah school culture, significantly contribute to the transformation of students' character and behavioral values. The outcomes indicate a positive shift towards humanist, tolerant, friendly, and democratic attributes among students.